A Description of the Statistical Methods for the Vaccine Impact on Diarrhea in Africa (VIDA) Study. (19th April 2023) - Powell, Helen; Liang, Yuanyuan; Neuzil, Kathleen M; Jamka, Leslie P; Nasrin, Dilruba; Sow, Samba O; Hossain, M Jahangir; Omore, Richard; Kotloff, Karen L
Abstract: Background: Diarrheal diseases remain a health threat to children in low- and middle-income countries. The Vaccine Impact on Diarrhea in Africa (VIDA) study was a 36-month, prospective, matched case-control study designed to estimate the etiology, incidence, and adverse clinical consequences of moderate-to-severe diarrhea (MSD) in children aged 0–59 months. VIDA was conducted following rotavirus vaccine introduction at 3 censused sites in sub-Saharan Africa that participated in the Global Enteric Multicenter Study (GEMS) ∼10 years earlier. We describe the study design and statistical methods of VIDA and where they differ from GEMS. Methods: We aimed to enroll 8–9 MSD cases every 2 weeks from sentinel health centers in 3 age strata (0–11, 12–23, 24–59 months) and 1 to 3 controls matched by age, sex, date of case enrollment, and village. Clinical, epidemiological, and anthropometric data were collected at enrollment and ∼60 days later. A stool specimen collected at enrollment was analyzed by both conventional methods and quantitative PCR for enteric pathogens. For the matched case-control study, we estimated the population-based, pathogen-specific attributable fraction (AF) and attributable incidence adjusted for age, site, and other pathogens, and identified episodes attributable to a specific pathogen for additional analyses. A prospective cohort study nested within the original matched case-control study allowed assessment of (1) the association between potential risk factors and outcomes other than MSD status and (2) the impact of MSD on linear growth. Conclusions: GEMS and VIDA together comprise the largest and most comprehensive assessment of MSD conducted to date in sub-Saharan Africa populations at highest risk for morbidity and mortality from diarrhea. The statistical methods used in VIDA have endeavored to maximize the use of available data to produce more robust estimates of the pathogen-specific disease burden that might be prevented by effective interventions. Abstract : We provide a description of the Vaccine Impact on Diarrhea in Africa (VIDA) study design, data collected, and a detailed explanation of the statistical methods, including where they differ from those of the study predecessor, the Global Enteric Multicenter Study.